Contending with vulnerability and uncertainty: what coaches say about coaching - Corsby, C. L.; Jones, R.; Lane, A. (Sports Coaching Review, 2023)
In exploring how coaches contend with their professional vulnerability, the purpose of this paper is three-fold. Firstly, to describe the informal rules of coaching that demand the appearance and expression of a certain persona. Secondly, to examine how such rules are tied to a culture of `the individual"; and, thirdly, to demonstrate how coaches` accounts of their work not only reflect, but also ensure such practices. The dataset emanated from 20 individual interviews with professional football coaches. Although taking full consideration of what the coaches actually said, the analysis sought to explore what the explanations were standing on behalf of; what Garfinkel described as an "official (professional) line". The findings pointed to coaches` necessity to `work hard`, to do things the `right way`, whilst limitedly acknowledging any vulnerability associated with the job. Positioned as a `greedy institution`, the narrative appeared as a means to contend with the difficulties coaches encountered.